Regulatory Mechanisms of the Resistance to Common Bacterial Blight Revealed by Transcriptomic Analysis in Common Bean (Phaseolus vulgaris L.) - Yang, Penghui; Chang, Yujie; Wang, Lanfen; Wang, Shumin; Wu, Jing (Frontiers in Plant Science, 2022)
Common bean blight (CBB), primarily caused by Xanthomonas axonopodis pv. phaseoli (Xap), is one of the most destructive diseases of common bean (Phaseolus vulgaris L.). The tepary bean genotype PI 319443 displays high resistance to Xap, and the common bean genotypes HR45 and Bilu display high resistance and susceptibility to Xap, respectively. To identify candidate genes related to Xap resistance, transcriptomic analysis was performed to compare gene expression levels with Xap inoculation at 0, 24, and 48 h post inoculation (hpi) among the three genotypes. A total of 1,146,009,876 high-quality clean reads were obtained. Differentially expressed gene (DEG) analysis showed that 1,688 DEGs responded to pathogen infection in the three genotypes. Weighted gene coexpression network analysis (WGCNA) was also performed to identify three modules highly correlated with Xap resistance, in which 334 DEGs were likely involved in Xap resistance. By combining differential expression analysis and WGCNA, 139 DEGs were identified as core resistance-responsive genes, including 18 genes encoding resistance (R) proteins, 19 genes belonging to transcription factor families, 63 genes encoding proteins with oxidoreductase activity, and 33 plant hormone signal transduction-related genes, which play important roles in the resistance to pathogen infection. The expression patterns of 20 DEGs were determined by quantitative real-time PCR (qRT-PCR) and confirmed the reliability of the RNA-seq results.